Mr. Radhesh Pant granted an interview to Mr. Bhai Raja Manandhar, Managing Editor, Hydro Nepal Journal. The interview in its entirety is presented. - Pant, Radhesh (Hydro Nepal: Journal of Water, Energy and Environment, 2015)
Not Available. DOI: http://dx.doi.org/10.3126/hn.v16i0.12226 HYDRO Nepal Journal of Water Energy and Environment Issue. 16, 2015, January Page: 48-51 Upload date: March 1, 2015